Freshwater fishes of Orissa, India - Mogalekar, Havagiappa Sharnappa; Canciyal, Johnson (Journal of Fisheries, 2018)
Varied freshwater resources of Orissa blessed with diverse fish fauna. In total, 186 species of fishes belonging to 11 orders, 33 families and 96 genera were recorded from various freshwater bodies of Orissa. Cypriniformes was the most dominant order and Cyprinidae was diverse family. The trophic level of fishes of Orissa ranged from 2.0 to 4.5 containing 62.41% of carnivorous species. Fishery status revealed existence of 120 species worth for capture fishery, 101 species worth for ornamental fishery, 37 species worth for culture fishery and 25 species worth for sport fishery. Threat status comprises of one Critically Endangered species, five Endangered species, three Vulnerable species and remaining 177 species were Not Threatened. The findings of present communication may serve as baseline information for planning, conservation and management of fish and fisheries resources of Orissa.